提升心臟加護護理人員執行生 理監視器參數設定之正確率. - 洪玉敏; 江金英; 黃暐茹; 莊月娥 (Tzu Chi Nursing Journal, 2019)
The aim of this project was to improve the accuracy of monitor settings in cardiac intensive care units (ICUs). The accuracy of monitor settings in this project was only 20.3%, and the identified reasons were as follows: the knowledge of nursing staff regarding the monitoring system was only 61.7%, the system was not setting correctly according to the alarm, the lack of bedside operation manuals, a complex operational interface, a nonstandard ward routine, and a lack of timely educational training. Our team developed the following strategies based on the analysis of the current situation: (1) Standardizing the operating and setting sequence of monitors, (2) setting the modules for cardiological parameters such as arrhythmia and ischemia, (3) making educational videos for monitor setting, and (4) periodic training and evaluation. The accuracy of monitor settings in a cardiac ICU improved from 20.3% to 92.2% immediately and to 94.8% by the third week due to the efforts of our team. The knowledge of nursing staff regarding the monitoring system also improved from 61.7% to 91.5%. The project significantly improved the technique of monitor setting in a cardiac ICU; this improvement can help medical teams swiftly handle changes in a patient's condition. The same strategies can be applied in other ICUs to build different parameter modules for varied specialties and to improve the quality of care for critically ill patients.